Influence of rice straw amendment on mercury methylation and nitrification in paddy soils. (February 2016) - Liu, Yu-Rong; Dong, Ji-Xin; Han, Li-Li; Zheng, Yuan-Ming; He, Ji-Zheng
Abstract: Currently, rice straw return in place of burning is becoming more intensive in China than observed previously. However, little is known on the effect of returned rice straw on mercury (Hg) methylation and microbial activity in contaminated paddy fields. Here, we conduct a microcosm experiment to evaluate the effect of rice straw amendment on the Hg methylation and potential nitrification in two paddy soils with distinct Hg levels. Our results show that amended rice straw enhanced Hg methylation for relatively high Hg content soil, but not for low Hg soil, spiking the same additional fresh Hg. methylmercury (MeHg) concentration was significantly correlated to the dissolved organic carbon (DOC) content and relative abundance of dominant microbes associated with Hg methylation. Similarly, amended rice straw was found to only enhance the potential nitrification rate in soil with relatively high Hg content. These findings provide evidence that amended rice straw differentially modulates Hg methylation and nitrification in Hg contaminated soils possibly resulting from different characteristics in the soil microbial community. This highlights that caution should be taken when returning rice straw to contaminated paddy fields, as this practice may increase the risk of more MeHg production. Main finding: Rice straw amendment enhanced both Hg methylation and nitrification potential in the relatively high, but not low, Hg soil. Highlights: Rice straw enhanced Hg methylation in relatively high Hg content paddy soils. Microbial community directly correlated to the Hg methylation. Mercury methylation in soils depend on Hg bioavailability and microbial activities. Hg input affects microbial community associated with decomposition of rice straw.